THE IMPACT OF HYPERGLYCEMIA FIRST DETECTED IN PREGNANCY ON OFFSPRING BLOOD PRESSURE IN SOWETO, SOUTH AFRICA. (April 2021) - Boerstra, Brittany; Soepnel, Larskse M.; Nicolaou, Veronique; Kolkenbeck-Ruh, Andrea; Ware, Lisa; Norris, Shane A.; Klipstein, Kerstin
Abstract : Objective: In South Africa, the prevalence of pediatric hypertension in 5-year-old children is 1 in 5. It has been estimated that 60% of South African children with elevated blood pressure maintain this status into adulthood, contributing to the highest prevalence of hypertension in adults aged 50+ globally. Recent literature suggests that pediatric hypertension may be influenced by maternal factors during pregnancy, including hyperglycaemia first detected in pregnancy (HFDP). The long-term consequences for offspring born to mothers with HFDP are not yet well understood and its impact on childhood blood pressure has not previously been assessed in sub-Saharan Africa. The objective of this study is to evaluate the association between HFDP and offspring blood pressure in 3–6-year-old children in Soweto, South Africa. Design and method: Oscillometric blood pressure was measured in 183 children born to mothers with and without HFDP using a 75-g 2-hour OGTT for diagnosis. Blood pressure was categorized into normotensive, elevated, Stage 1 and Stage 2 hypertension according to the 2017 American Academy of Pediatrics Hypertension Guidelines. The association between maternal hyperglycemia and offspring blood pressure was analyzed using multiple linear regression Results: In 48.6% of children, blood pressure was above the normotensive range. Prevalence of hypertension did not significantly differ between the exposed and control group. There was no significant association between maternal hyperglycemia and offspring systolic blood pressure when adjusted for offspring age, height, and sex, [-0.323, 95% CI (-3.126–2.480), P = 0.821). Early life factors, including child BMI age z-score [1.529, 95% CI (0.067–2.990), P = 0.041] and exposure to maternal smoking [5.460, 95% CI (0.182–10.739), P = 0.043], were significantly associated with offspring systolic blood pressure. Maternal hypertension was not a significant predictor for offspring blood pressure. Conclusions: Maternal HFDP was not associated with childhood blood pressure at 3–6 years, but the high prevalence of pediatric hypertension in this group of preschool-aged children is concerning. Future research should further evaluate offspring obesity and maternal smoking as potentially preventable risk factors that could be improved by public policy to reduce the cycle of hypertension and cardiovascular risk in an African setting.